Study of the impact of load-following operation on light water reactor fuel performance using the TRANSURANUS code - Rathore, Vikram; Blair, Paul; Robertson, Gustav; Jonson, Martin; Andersson, Peter (Frontiers in Energy Research, 2025)
Small modular reactors (SMRs) are gaining popularity due to several economic and safety benefits, along with their desirable load-following capability, which allows them to complement intermittent renewable energy sources. However, the impact of load-following operation on fuel performance remains underexplored. This study uses the fuel performance code, TRANSURANUS, to assess the effects of such operations on pressurized water reactor (PWR) fuel performance, given the design similarities between many SMRs and large light water reactors (LWRs). Hypothetical load-following operations were simulated using varying linear heat rate levels, neutron flux, and coolant flow rate, in accordance with a parameterized load-following operation. Most fuel performance parameters remained below safety limits. However, in some cases, the pellet–cladding interaction–stress corrosion cracking (PCI–SCC) model (SPAKOR) predicted cladding cracks and failures that were not observed during regular reference operation. A sensitivity analysis of load-following parameters indicated minimal deviations in fuel performance, apart from the PCI–SCC-related issues.